The evolution of reason : logic as a branch of biology - Cooper, William S. (Cambridge studies in philosophy and biology., 2001)
"Formal logic has traditionally been conceived as bearing no special relationship to biology. Recent developments in evolutionary theory suggest, however, that the two subjects may be intimately related. In this book, William Cooper presents a carefully supported theory of rationality in which logical law is seen as an intrinsic aspect of the process of evolution. This biological perspective on logic, though at present unorthodox, suggests new evolutionary foundations for the study of human and animal reasoning."